The influence of the television programme, 'Studiemetodes' on the study habits and attitudes of a group of standard six and seven pupils - Morgan, Lynette Charlotte (Stellenbosch : Stellenbosch University, 2012)
Advanced project (M.A.) -- University of Stellenbosch, 1988.